The Development of English Communication Skills for Staff Working in Tourist Industry in Khon Kaen Province: A Pioneering-Case Study at Khok Sa Nga Village and Chang Kra Temple - Seetrakarn, Napak-on (วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย; Vol 10 No 1 (2018): วารสารมนุษยศาสตร์ มหาวิทยาลัยมหามกุฏราชวิทยาลัย, 2021)
This research project has been conducted as an extension of a previous study by Piriyasilpa Y. (2014). It proposed the contents for the short-training course of English for staff members whose work is related to the tourist industry. In this study, the training contents were prepared with the aim to improve the participants’ English communication skills. The pioneering areas included Khok Sa Nga village, Nampong district and Chang Kra temple, Muncha Kiri district. In total, there were sixty participants, thirty from each of the two districts involved. The results showed that all of the participants had a high satisfaction toward the training, and that all of them have improved their post-test marks. Moreover, some of the participants have made comments regarding the facilities and travels. These comments will be useful and taken into account when extending the project to wider community areas. Based on the findings, it could be concluded that this short-training course for English communication skills is useful and beneficial to the participants, and that the pattern of training as well as contents can be useful for the construction of other short-training courses in different communities.